1974
DOI: 10.1002/jss.400020225
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of flagellar formation and function

Abstract: The basal structure of the flagellum controls both activity and assembly. In order to define the steps involved in these processes, genetic analysis was performed. Twenty genes were found t o be required for the complete assembly and function of the organelle. FlaE controls the length of the hook, flaA is required both t o maintain flagellar structure and for chemotaxis, and flaI plays a role in regulating the synthesis of the entire structure. Mutations mapping close to flaI (the cfs mutations) release flagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…To identify the triplet protein with one of the polypeptides involved in flagellar structure or function, it was compared to the polypeptide component of the flagellar basal structure which has an apparent molecular weight of 59,000 on acrylamide gels (7) and to the MCP described by Kort et al (9) which has also been reported to have an apparent molecular weight of 60,000. These radioactive polypeptides were compared by polyacrylamide gel electrophoresis under a variety of conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the triplet protein with one of the polypeptides involved in flagellar structure or function, it was compared to the polypeptide component of the flagellar basal structure which has an apparent molecular weight of 59,000 on acrylamide gels (7) and to the MCP described by Kort et al (9) which has also been reported to have an apparent molecular weight of 60,000. These radioactive polypeptides were compared by polyacrylamide gel electrophoresis under a variety of conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been unclear whether the target of the glucose effect is flagellin synthesis or some step in flagella assembly. Recently a mutant of E coli, eft, has been isolated, which releases flagella fo rmation from catabolite repression (57,154), and the phenotype of this mutant has led Silverman and Simon to suggest that flagella structural proteins are catabolically repressed either directly or indirectly. In contrast to the inhibitory effect of 10 mM glucose on flagella fo rmation in E. coli and S. typh imurium, glucose (up to 0.1 M) does not inhibit flageJla fo rmation or motility in C crescentus grown on defined minimal Annu.…”
Section: Flagella and Pili Biogenesismentioning
confidence: 98%
“…It is composed of a long helical filament and a complex basal structure which is tightly bound to the outer membrane of the cell. The basal structure has been purified (9) and its components were characterized by gel electrophoresis. It was found to contain eleven different polypeptide chains (10).…”
mentioning
confidence: 99%